2022
DOI: 10.3389/fpls.2022.1000430
|View full text |Cite
|
Sign up to set email alerts
|

Selenium enhances chilling stress tolerance in coffee species by modulating nutrient, carbohydrates, and amino acids content

Abstract: The effects of selenium (Se) on plant metabolism have been reported in several studies triggering plant tolerance to abiotic stresses, yet, the effects of Se on coffee plants under chilling stress are unclear. This study aimed to evaluate the effects of foliar Se application on coffee seedlings submitted to chilling stress and subsequent plant recovery. Two Coffea species, Coffea arabica cv. Arara, and Coffea canephora clone 31, were submitted to foliar application of sodium selenate solution (0.4 mg plant–1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…Participation of Se in carbohydrate metabolism is known to stimulate plant antioxidant defense and improve the nutritional quality of the product [ 29 ]. In this respect, a significant increase in monosaccharide content in horseradish roots as a result of Se supply represents an important characteristic of horseradish, suggesting the existence of a disaccharide hydrolysis process ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participation of Se in carbohydrate metabolism is known to stimulate plant antioxidant defense and improve the nutritional quality of the product [ 29 ]. In this respect, a significant increase in monosaccharide content in horseradish roots as a result of Se supply represents an important characteristic of horseradish, suggesting the existence of a disaccharide hydrolysis process ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Selenium is not considered a nutrient for plants, but it has beneficial effects, such as reducing the stress caused by low temperatures in coffee [ 14 ], increasing the yield of wheat [ 15 ], increasing protein and amino acid content in soybean [ 16 ], and reducing drought stress in common bean plants [ 17 ]. Its effects on plants have been studied for approximately 70 years, and several advantages have already been reported [ 14 , 18 , 19 , 20 , 21 ]. Due to its beneficial effects on plants, recently a change of the definition of “plant nutrient” has been proposed to start a debate on the inclusion of Se, and other beneficial elements, as a plant nutrient [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is not considered a nutrient for plants, but it has beneficial effects, such as reducing the stress caused by low temperatures in coffee [14], increasing the yield of wheat [15], increasing protein and amino acid content in soybean [16], and reducing drought stress in common bean plants [17]. Its effects on plants have been studied for approximately 70 years, and several advantages have already been reported [14,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is one of the promising approaches to fight the metabolic responses in plants under this type of adverse condition [14][15][16]. Selenium is not a plant nutrient, but several studies have reported its beneficial effects, mainly under stress conditions (e.g., salinity, chilling stress, metals accumulation, and drought stress) [11,[17][18][19]. The extensive antioxidant capacity of Se arises from its ability to enhance selenoproteins, like glutathione peroxidase.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of Se application in plants, some authors have noticed an increase in shoot and root biomass and better plant development [25], as well as improved regulation in the status of water, and higher antioxidant apparatus activation in water-stressed crops [26]. Sousa et al [19] found that Se can modulate nutrient uptake, carbohydrate breakdown, and enzymatic activity in coffee plants after low-temperature stress, helping the plants to overcome adverse conditions. Assessing the effect of foliar Se supply in coffee plants cultivated in field conditions, Mateus et al [27] found that Se can protect the photosynthetic pigments and increase coffee bean yield.…”
Section: Introductionmentioning
confidence: 99%